2014
DOI: 10.1155/2014/852681
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography in the Postchemotherapy Management of Patients with Seminoma: Systematic Review and Meta-Analysis

Abstract: Objective. To meta-analyze published data about the diagnostic performance of fluorine-18-Fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) and PET/computed tomography (PET/CT) in the postchemotherapy management of patients with seminoma. Methods. A comprehensive literature search of studies published through January 2014 on this topic was performed. All retrieved studies were reviewed and qualitatively analyzed. Pooled sensitivity and specificity, positive and negative predictive values (PPV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 26 publications
1
33
0
4
Order By: Relevance
“…Similar results were found by Treglia et al . showing a pooled sensitivity of 78% (95% CI 67–87), a specificity of 86% (95% CI 81–89), a PPV of 58% (95% CI 48–68), an NPV of 94% (95% CI 90–96) and an accuracy of 84% (95% CI 80–88) for 18 F‐FDG PET/CT . Based on these results, it can be concluded that negative 18 F‐FDG PET/CT findings of residual masses after chemotherapy in metastatic seminoma warrant follow up, whereas positive findings should lead to subsequent treatment, such as salvage surgery, as mentioned by current guidelines .…”
Section: Testicular Cancermentioning
confidence: 84%
See 1 more Smart Citation
“…Similar results were found by Treglia et al . showing a pooled sensitivity of 78% (95% CI 67–87), a specificity of 86% (95% CI 81–89), a PPV of 58% (95% CI 48–68), an NPV of 94% (95% CI 90–96) and an accuracy of 84% (95% CI 80–88) for 18 F‐FDG PET/CT . Based on these results, it can be concluded that negative 18 F‐FDG PET/CT findings of residual masses after chemotherapy in metastatic seminoma warrant follow up, whereas positive findings should lead to subsequent treatment, such as salvage surgery, as mentioned by current guidelines .…”
Section: Testicular Cancermentioning
confidence: 84%
“…8 94% (95% CI 90-96) and an accuracy of 84% (95% CI 80-88) for 18 F-FDG PET/CT. 9 Based on these results, it can be concluded that negative 18 F-FDG PET/CT findings of residual masses after chemotherapy in metastatic seminoma warrant follow up, whereas positive findings should lead to subsequent treatment, such as salvage surgery, as mentioned by current guidelines. 2 In order to avoid false positive findings as a result of chemotherapy-induced inflammatory and granulomatous tissues, or false negative results as a result of temporary suppression of tumor cell activities, at least 6 weeks between the end of chemotherapy and 18 F-FDG PET/CT examination should be respected.…”
Section: Introductionmentioning
confidence: 89%
“…One systematic review and meta-analysis including 4 selected studies with a total of 130 patients evaluated the diagnostic accuracy of 18 F-FDG PET/CT for prediction of viable residual tumors after chemotherapy in patients with metastatic seminoma and demonstrated that it was superior to CT for determining tumor size and predicting tumor viability: sensitivity was 72 vs 63 %, specificity was 92 vs 59 %, positive predictive value (PPV) was 70 vs 28 %, and negative predictive value (NPV) was 93 vs 86 %, respectively [96]. Another recent systematic review and meta-analysis including 9 selected studies with a total of 375 patients showed that 18 F-FDG PET/CT had a pooled sensitivity of 78 % (95 % CI: 67–87 %), a specificity of 86 % (95 % CI: 81–89 %), a PPV of 58 % (95 % CI: 48–68 %), a NPV of 94 % (95 % CI: 90–96 %), and an accuracy of 84 % (95 % CI: 80–88 %) [97]. Based on these results, it can be concluded that negative 18 F-FDG PET/CT findings warrant follow-up if only to avoid inappropriate subsequent treatment (surgery, chemotherapy, or radiotherapy), whereas positive 18 F-FDG PET/CT findings suggest a high possibility of residual seminoma, though a false-positive result cannot be excluded in view of the low PPV.…”
Section: Testicular Cancermentioning
confidence: 99%
“…Several prospective and retrospective studies evaluated the diagnostic performance of FDG-PET or PET/CT in the post chemotherapy management of patients with GCT 70,72,7584 . Recently, Treglia et al published a meta-analysis about the diagnostic performance of FDG PET and PET/CT in the post chemotherapy management of patients with seminoma 85 . Nine studies including 375 scans were included.…”
Section: Use Of Pet In Testicular Cancermentioning
confidence: 99%